The brain, reading and the homo videns - Arboccó de los Heros, Manuel (2016)
The following essay introduces a number of researches, reflections, and quotes extremely relevant onareas such as neuroscience, pedagogy and psychology. Each area specializes in certain subjects but,in some moment, they meet and share common ground, nourish each other and help us understandmore and more the complex world of knowledge, the functioning of the brain and the human behavior.Our concern today is the decline of the word, reading and its possibilities, as well as the increase ofmedia interests such as the television that has deeply depreciated in the last three decades. We believethat certain trendy practices today have not contributed to improve our production and intellectuality;instead, said practices have led to an alarming mental impoverishment easy to observe in teenagers(even undergraduate students) and children.We will start recalling some general discoveries in the field of neuroscience, then we will deal with theimpact of postmodern life and technology misused in the impairment of cognitive (and affective) systemof the homo sapiens, or –as Giovanni Sartori would say– the “homo videns”, since it has become adependent being of visual stimuli, to the detriment of thinking, abstraction and deep reading.Finally, we also hope these reflections will arouse interest and boost new thoughts.